2022
DOI: 10.3389/fpsyg.2022.1011787
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of appearance on the impact of performance rankings in the live streaming market

Abstract: The live streaming market is becoming increasingly competitive, and relative performance information regarding broadcasters is available to all participants in the live streaming industry, exacerbating the level of competition. Using data from 42,166 live streams by 293 broadcasters, we investigated two benefits of relative performance information in relation to the live streaming business and how these effects vary when the broadcaster appears competent, trustworthy, likable, or attractive. On the basis of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Previous studies have mainly concentrated on using "stimulus organism-response" model (SOR) [11], theory of planned behavior (TPB) [12], and technology acceptance model (TAM) [13] to understand how platforms are used to sell goods or services and attract tips from viewers through livestreaming. The identified factors for viewer tipping in live stream shows include viewer engagement [14], perceived utilitarian, hedonic, and symbolic value of live streaming shows [15,16], live streamers' characteristics such as attractiveness and source credibility [17][18][19][20], and social interactions [21][22][23][24]. Unlike viewers of e-commerce-focused live streaming whose primary motivations are linked to the products advertised, viewers of pan-entertainment live streaming shows purchase virtual gifts to foster romantic connections with streamers and to display a good image of other viewers [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly concentrated on using "stimulus organism-response" model (SOR) [11], theory of planned behavior (TPB) [12], and technology acceptance model (TAM) [13] to understand how platforms are used to sell goods or services and attract tips from viewers through livestreaming. The identified factors for viewer tipping in live stream shows include viewer engagement [14], perceived utilitarian, hedonic, and symbolic value of live streaming shows [15,16], live streamers' characteristics such as attractiveness and source credibility [17][18][19][20], and social interactions [21][22][23][24]. Unlike viewers of e-commerce-focused live streaming whose primary motivations are linked to the products advertised, viewers of pan-entertainment live streaming shows purchase virtual gifts to foster romantic connections with streamers and to display a good image of other viewers [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…With the stride of network advancement, online communities have thrived as pivotal venues for public engagement and exchange, creating novel avenues for individuals' learning, socializing and collective pursuits [1,2]. Integrated deeply into these cyberspaces, webcasting has attracted growing users with its real-time interactivity to shape a distinctive cultural phenomenon [3,4].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Previous studies have found that in the service industry, the appearance of service providers could in uence users' behavior. For example, in the live-streaming industry, the appearance of the host positively moderated the relationship between the host's effort and live performance [11]. However, there is currently no uni ed research conclusion on the in uence of appearance in professional elds.…”
mentioning
confidence: 99%